Práticas de letramento: o processo de alfabetização em turmas do 1º ano do Ensino Fundamental na EMEF Waldir Ribeiro de Almeida do município de Novo Repartimento - PA - SOUSA, Maria Eliane Evangelista de (2021)
This paper discusses the process of literacy and literacy with the objective of analyzing literacy practices for reading formation at Waldir Ribeiro de Almeida Municipal School. For this, a bibliographical and field research was carried out with 05 teachers in the 1st year of elementary school in the Municipal School of Waldir Ribeiro de Almeida in Novo Repartimento - PA. The results point out the importance of reading an enriching source of knowledge and information in the formation of the individual, with this requires that teaching methodologies that stimulate the pleasure of reading to construct writing be promoted. The study is conclusive, the practice of reading for the formation of the individual contributes to the construction of permanent habits, showing how reading can be a great ally in the process of literacy and literacy. It is known that children are fascinated by stories and that these favor their cognitive, intellectual, emotional and social development. The purpose of this study was to confirm the need for reading in first-year classes in elementary school as a form of social transformation.